Gait Recognition Based on Deep Learning - Jameel, Humam Khaled; Dhannoon, Ban Nadeem (Iraqi Journal of Science, 2022)
In current generation of technology, a robust security system is required based on biometric trait such as human gait, which is a smooth biometric feature to understand humans via their taking walks pattern. In this paper, a person is recognized based on his gait's style that is captured from a video motion previously recorded with a digital camera. The video package is handled via more than one phase after splitting it into a successive image (called frames), which are passes through a preprocessing step earlier than classification procedure operation. The pre-processing steps encompass converting each image into a gray image, cast off all undesirable components and ridding it from noise, discover difference between two successive images to discover the place motion occurs, converting the result to a binary image, and finally use morphological operation to close holes resulted from the previous steps. The last and most important stage in the system is the classification stage, which depends on deep neural network. The results obtained indicate a high quality of performance and an accuracy of 99.5%.